ER, PR & HER2 Receptor status in recurrent breast cancer: Its relation to age & time of recurrence (Journal of Surgical Sciences, 2020)
Background: Malignant neoplastic lesions of the breast are one of the main causes of cancer death among women. In tumor cells the expression status of Estrogen receptor (ER), progesterone receptor (PR), and c-ERBB2 (HER2/neu) are therapeutically and prognostically important markers affecting the treatment approach, management and prognosis of breast carcinoma.Objective: To explore the relation of receptor status in recurrent breast cancer to age and time of recurrence. Methods: This study was conducted in National Institute of Cancer Research and Hospital (NICRH) and included 81 female patients between 20 to 75 years with recurrent breast cancer. Detection of receptor status of ER +ve/-ve, PR +ve/-ve, Her-2+ve/-ve was based on the immunohistochemistry staining of tissue samples of malignant neoplastic lesions prepared from tissue biopsies of patients with recurrent breast cancer. All the information were recorded through the pre-structured data collection sheet and analyzed.Results: This study showed that most of the recurrent breast cancer patients were Triple negative breast cancer (TNBC) (39.5%) and among them most of them were younger patients. Younger patients with TNBC had increased risk of recurrence. Most of the recurrence occurred within 1-2 years.Conclusion: It can be concluded that the assessment of the expression of these biornarkers in recurrent tumors provides reliable information for the treatment approach of locoregional tumors.Journal of Surgical Sciences (2018) Vol. 22 (1): 16-20